2001
DOI: 10.1080/08035250152708743
|View full text |Cite
|
Sign up to set email alerts
|

Hyperimmune bovine colostrum in the treatment of shigellosis in children: a double-blind, randomized, controlled trial

Abstract: The results indicate that HBC as an adjuvant is unable to show any beneficial effect in reducing the stool frequency, duration or severity of childhood shigellosis due to S. dysenteriae type I infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Similar preparations from non-immunized cows may provide protection against bacterial toxins that are the cause of diarrhea in AIDS patients [68]. These studies, along with the above mentioned study comparing colostrum preparations from cows immunized against S. dysenteriae or non-immunized cows [63], demonstrate that bovine colostrum contains significant antimicrobial properties as a result of natural exposure of the cows to antigens of pathogens that may afflict humans.…”
Section: Immune Milkmentioning
confidence: 96%
See 1 more Smart Citation
“…Similar preparations from non-immunized cows may provide protection against bacterial toxins that are the cause of diarrhea in AIDS patients [68]. These studies, along with the above mentioned study comparing colostrum preparations from cows immunized against S. dysenteriae or non-immunized cows [63], demonstrate that bovine colostrum contains significant antimicrobial properties as a result of natural exposure of the cows to antigens of pathogens that may afflict humans.…”
Section: Immune Milkmentioning
confidence: 96%
“…Consumption of a hyperimmune immunoglobulin concentrate with a high antibody titer against a lipopolysaccharide isolated from Shigella flexneri 2a also has been shown to provide protection against a challenge with the same strain [62]. However, no difference in diarrhea or other symptoms in children with stools positive for S. dysenteriae was found whether treated with bovine colostrum from cows immunized against S. dysenteriae or with colostrum from cows not hyperimmunized [63]. …”
Section: Immune Milkmentioning
confidence: 99%
“… 22 23 The impact of bovine colostrum on paediatric bacterial enteritis has not been clearly demonstrated; Huppertz et al found a reduced stool frequency in thirteen German patients with E. coli enteritis, but no impact of hyperimmune colostrum was observed in Bangladeshi children with enteropathogenic E. coli or ETEC associated diarrhoea, nor in children infected with Shigella. 24–26 …”
Section: Discussionmentioning
confidence: 99%
“…Values were not significantly different between groups. They concluded that HBC as an adjuvant is unable to show any beneficial effect in reducing the severity of childhood shigellosis [32]. …”
Section: Discussionmentioning
confidence: 99%